The Effect Of Work Motivation And Specialist Development On Career Development With Knowledge Sharing Mediation - sananta maldhe; Prayekti Prayekti; Didik Subiyanto (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
Research Aims: This study aims to analyze the relationship between work motivation, specialist development, knowledge sharing, and career development in an organizational context.Design/Methodology/Approach: This research employs a quantitative method with a survey approach to collect data from selected respondents. The primary instrument is a questionnaire using a 5-point Likert scale, enabling respondents to express their level of agreement with statements related to the studied variables. Data analysis utilizes Structural Equation Modeling (SEM) with AMOS software, chosen for its ability to analyze complex causal relationships and test conceptual models based on underlying theories. The sample was selected using a Stratified Random Sampling technique from a population of 10,977 police personnel at Polda DIY, with a final sample of 151 respondents.Research Findings: The results indicate that work motivation significantly influences knowledge sharing, which in turn contributes to career development. High work motivation encourages active engagement in information exchange and experience-sharing, fostering an environment that supports innovation and competency enhancement. In contrast, specialist development has a more limited impact on knowledge sharing and career development, particularly when acquired skills are overly specific and less flexible for various job roles. Moreover, knowledge sharing mediates the relationship between work motivation and career development, highlighting its crucial role in strengthening career growth.Theoretical Contribution/Originality: These findings suggest that organizations should foster a knowledge-sharing culture and balance specialist development with collaborative skills, ensuring workforce competitiveness in an increasingly dynamic work environment